Pertikaian sempadan di Pantai Timur Borneo Utara pada tahun 1878 hingga 1915 : satu kajian pengurusan diplomasi antara British dan Belanda - Mat Zin, Mat Kib (2017)
This study discusses the history of border disputes between the British and the Dutch in the East Coast of North Borneo from 1878 until 1915. The disputes involving the Borneo territories, especially in North Borneo, began in the early 1800s. They should have been solved through a series of meetings in the Proceedings of the Joint Commission for deliberation of the Boundaries between the Netherland Indian Possessions on the Island of Borneo and the Territory belonging to the British North Borneo Company, 1889 and the 1891 Convention. Nevertheless, the problems were resolved amicably through the 1951 Agreement. The Dutch had occupied the Borneo region, especially Bulungan in the 17th century. Since then, there had been several border disputes between the Netherlands and the Sultanate of Bulungan. There was an attempt to resolve the dispute through the Contract of Vassalage of 1850 and 1878. Disputes in the Borneo territories became even more acute with the cession of territory by the Sultan of Sulu to Overbeck and Dent Association through the Grant of January the 22nd 1878. This cession led to persistent disputes between the British and Dutch in the East Coast of North Borneo. This study examines the history of management of border disputes between Britain and the Netherlands, through a series of meetings held in 1889, 1891 and 1915, using qualitative methods and historical approach. The materials for the study were obtained through library research. Most of the primary sources were official British records found in the British National Archives, Kew, London, the Malaysian National Archives and Sabah State Archives. Also included were official documents used in the International Court of Justice relating to border disputes between Malaysia and Indonesia. The secondary resources referred to include books, journals and newspapers. The finding of the study shows that the British-Dutch border disputes in the East Coast of Borneo were resolved through meetings and conventions. The study also finds that diplomacy was employed to resolve the border disputes in 1889, 1891 and 1915. The findings of this study are important because it can be used a vis a vis on managing border disputes especially from a historical perspective. The findings can also be used as reference for Malaysia in dealing with border disputes over the Layang-Layang Island, Spratly Islands, Limbang and the Philippines claim on Sabah, now and in the future. Keywords: British, Dutch, East